Thermoelectric Generators as a Heat Recovery System for Exhaust Gases of Vehicles Driving at Low Speeds - A. Al-Janabi; O. Al Salmi; E. Al Subhi; A. Al Hadhrami (Engineering and Technology Journal, 2023)
To save the environment and utilize the waste heat associated with exhaust gases of internal combustion engines, it is crucial to design an efficient system that can recover this heat loss and convert it into useful energy. This study is devoted to developing, through an experimental approach, a practical technical solution to minimize the waste heat of the exhaust gases and convert it into a source of power for further applications in the vehicle. Six thermoelectric generators (TEG1-1263-4.3) were attached to the exhaust pipe in an arrangement of three connected in parallel and three connected in series. The thermoelectric generators were in a square shape of size 30 mm x 30 mm, and operated at a maximum temperature of 320. The experiments were conducted for a vehicle speed limit between (10 km/h - 60 km/h). It has been found that at a vehicle speed of 55 km/h, the exhaust pipe surface temperature reached approximately 116oC. For six models of TEGs, the output voltage was 4.13 volts. And the system efficiency was found to vary between 3.6% -15.9%, depending on the surface temperature of the exhaust pipe, i.e., the surface temperature that is in contact with the hot side of the thermoelectric generators. Such outputs refer to the efficiency of TEGs to be used as a heat recovery system. Furthermore, the produced power can be used for feeding other applications within the vehicle, such as using a small fridge for a cooling process.